A Study of Peace Culture in Opportunity Expansion Schools in Thailand - Tepamat, Patama; Thawinkarn, Dawruwan (International Journal of Psychosocial Rehabilitation, 2024)
This research aims to study components of peace culture in the opportunity expansion schools under the office of the Basic Education Commission, Thailand. Using descriptive research on 2 steps, 1) study 13 documents about peace culture for synthesis of the components of peace culture, and 2) confirm the components by the 7 experts in education administration. The research found that: The peace culture of the opportunity expansion schools consisted of 4 main components, including: 1) Trust consists of 3 subcomponents: satisfaction, integrity and compassion 2) Share-value consists of 3 subcomponents: organizational requirements, common practice and common norms 3) Collaboration consists of 3 subcomponents: teamwork, network building and creating personal relationships 4) Respect consists of 3 subcomponents: self-respect, accepting others, and appreciation of the environment